Tire inspection spreading machine - Penno, Pawel (2016)
The aim of the project was to design in Solidworks and improve an existing Tire inspection machine. The project was developed in Gislotica - Mechanical Solutions, guided by ing. Rui Manuel Fazenda Silva who is a professor in ISEP. The designed device relates to the inspection of automobile tires for holes and weak places caused by punctures and usage. Such inspection includes careful examination of the inside surface of the tire which is difficult because of its cylindrical shape, stiff and resistant nature of the material out of which the tire is made. The whole idea is to provide a machine by which the walls of the tire may be spread and hold apart, presenting the inner surface for the worker to control. The device must also perform rotational and vertical movement of the tire. It is meant to provide inspection in hich there is no need for the controller to use force. It makes his work easier and more efficient.